Epidemiology of American Tegumentary Leishmaniasis and Trypanosoma cruzi Infection in the Northwestern Argentina - Hoyos, Carlos Lorenzo (2016)
Background. Endemic areas of tegumentary leishmaniasis (TL) in Salta, Argentina, present some overlap zones with the geographical distribution of Chagas disease, with mixed infection cases being often detected. Objectives. The purpose of this study was to determine the magnitude of Leishmania sp. infection and potential associated risk factors, the serologic prevalence of T. cruzi, and the presence of T. cruzi-Leishmania sp. mixed infection in a region of the northwest of Argentina. Methods. Cross-sectional studies were conducted to detect TL prevalence and T. cruzi seroprevalence. A case-control study was conducted to examine leishmaniasis risk factors. Results. Prevalence of TL was 0.17%, seroprevalence of T. cruzi infection was 9.73%, and mixed infection proportion - within the leishmaniasic patients group - was 16.67%. The risk factors associated with TL transmission were sex, age, exposure to bites at work, staying outdoors more than 10 hours/day, bathing in the river, and living with people who had lesions or were infected during the study. Discussion. The endemic pattern of TL seems to involve exposure of patients to vectors in wild as well as peridomestic environment. Cases of T. cruzi infection are apparently due to migration. Therefore, a careful epidemiological surveillance is necessary due to the contraindication of antimonial administration to chagasic patients.